Anybody can do Value at Risk: A Teaching Study using Parametric Computation and Monte Carlo Simulation - Yun Hsing Cheung; Robert J Powell (Australasian Accounting, Business and Finance Journal, 2013)
The three main Value at Risk (VaR) methodologies are historical, parametric and Monte Carlo Simulation. Cheung & Powell (2012), using a step-by-step teaching study, showed how a nonparametric historical VaR model could be constructed using Excel, thus benefitting teachers and researchers by providing them with a readily useable teaching study and an inexpensive and flexible VaR modelling option. This article extends that work by demonstrating how parametric and Monte Carlo Simulation VaR models can also be constructed in Excel, thus providing a total Excel modelling package encompassing all three VaR methods.
Keywords: Value at risk; Parametric value at risk; Monte Carlo simulation; Financial modelling; Pseudo-random number generator